Condensazione aldolica e visual thinking: Come usare sketchnotes per descrivere un percorso teorico-sperimentale di Green Chemistry - Castiglioni, Giulia (Chimica nella Scuola, 2024)
An alternative to the implementation of the classic lab notebook is proposed, in which visualization and schematization strategies are carried out in the inclusive view toward students preferring pencil over pen, drawing over text. Everything is included in a Green Organic Chemistry pathway, based on the carbonyl compounds and related aldol synthesis.